Republic of Korea : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, Corporate Governance, and Payment Systems. (IMF Staff Country Reports; Country Report ;, 2003)
This paper presents key finding of the Financial System Stability Assessment for the Republic of Korea, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, Corporate Governance, and Payment Systems. Korea has achieved a high degree of observance of key standards and codes through newly revised laws and competent supervision. However, supervisory independence could be strengthened to improve the ability to provide authoritative guidance and interpretation. Reform of the banking sector has restored profitability and improved its strength and resilience.